(untitled) (Research, Society and Development, 2021)
Objective: to identify and analyze the scientific production on the evolution of COVID-19 in pregnant/puerperal women according to skin color/race. Methodology: this is an Integrative Literature Review (ILR), with a search in the EMBASE, LILACS, PUBMED/MEDLINE and Web of Science databases conducted in February 2021. From the PICO strategy the research question was constructed: Is there evidence that black pregnant women/puerperal women with COVID-19, treated in a hospital setting, when compared to white pregnant women, evolve with more severity (need for admission to the Intensive Care Unit/death)? The terms indexed in the structured vocabulary of the Health Sciences Descriptors (DeCS) and Medical Subject Headings (MeSH terms) were used: "COVID-19" OR "2019-nCoV" AND "Pregnant Woman" OR "Prenatal Care" OR "pregnancy" AND "Race" OR "Racial Groups" OR "Racism" OR "Social Inequities" OR "African American" AND "Hospitalization" OR "Inpatient Unit" AND "Death" OR "Causes of Death" OR "Maternal Death" OR "Intensive Care Units". Results: Six studies were identified, conducted in the United States of America (three studies), United Kingdom (one study), and Brazil (two studies), and only one of them was classified as level of evidence 4, the others as level 6. All studies were observational, often with small samples and varied ethnic groups, not allowing effective conclusions. Two Brazilian studies that used secondary, population-based databases found black race/color to be a risk factor for severe COVID-19. Conclusion: With the studies analyzed, it was not possible to establish a clear relationship between race/color and negative outcomes (need for admission to the intensive care unit/death) of COVID-19 among pregnant/puerperal women.